On the Institution of Public Hearing – An Analysis from the Theoretical Point of View and the Perspective of the State’s Political Practice (Fifth to Ninth Term of the Sejm of the Republic of Poland) - Bogusław Przywora; Małgorzata Wróblewska (Krytyka Prawa)
The purpose of the study is to evaluate the public hearings’ role in law-making. The study addresses the problem of whether the institution of public hearing is an instrument that has a real impact on the law-making process. The discussion that follows takes into consideration, on the one hand, the theoretical issues concern-ing the institution of public hearings and, on the other hand, the Polish state’s poli-tical practice of using public hearings (based on statistical data on the application of this institution covering the fifth to ninth term of the Sejm of the Republic of Poland). The state’s political practice dating to this period shows that Sejm commit-tees were abstemious in using this instrument. Since the regulation’s entry into force on this institution covers the period from the fifth to the end of the ninth term of the Sejm, only 34 public hearings covering 46 bills out of 5855 bills have been organised. It provides the basis for the conclusions and propositions de lege ferenda.